Malaria in pregnancy in India: a 50-year bird’s eye - Kojom Foko, Loick Pradel; Singh, Vineeta (Frontiers in Public Health, 2023)
Introduction In 2021, India contributed for 79% of malaria cases and 83% of deaths in the South East Asia region. Here, we systematically and critically analyzed data published on malaria in pregnancy (MiP) in India. Methods Epidemiological, clinical, parasitological, preventive and therapeutic aspects of MiP and its consequences on both mother and child were reviewed and critically analyzed. Knowledge gaps and solution ways are also presented and discussed. Several electronic databases including Google scholar, Google, PubMed, Scopus, Wiley Online library, the Malaria in Pregnancy Consortium library, the World Malaria Report, The WHO regional websites, and ClinicalTrials.gov were used to identify articles dealing with MiP in India. The archives of local scientific associations/journals and website of national programs were also consulted. Results Malaria in pregnancy is mainly due to Plasmodium falciparum (Pf) and P. vivax (Pv), and on rare occasions to P. ovale spp. and P. malariae too. The overall prevalence of MiP is 0.1–57.7% for peripheral malaria and 0–29.3% for placental malaria. Peripheral Pf infection at antenatal care (ANC) visits decreased from 13% in 1991 to 7% in 1995–1996 in Madhya Pradesh, while placental Pf infection at delivery unit slightly decreased from 1.5% in 2006–2007 to 1% in 2012–2015 in Jharkhand. In contrast, the prevalence of peripheral Pv infection at ANC increased from 1% in 2006–2007 to 5% in 2015 in Jharkhand, and from 0.5% in 1984–1985 to 1.5% in 2007–2008 in Chhattisgarh. Clinical presentation of MiP is diverse ranging from asymptomatic carriage of parasites to severe malaria, and associated with comorbidities and concurrent infections such as malnutrition, COVID-19, dengue, and cardiovascular disorders. Severe anemia, cerebral malaria, severe thrombocytopenia, and hypoglycemia are commonly seen in severe MiP, and are strongly associated with tragic consequences such as abortion and stillbirth. Congenital malaria is seen at prevalence of 0–12.9%. Infected babies are generally small-for-gestational age, premature with low birthweight, and suffer mainly from anemia, thrombocytopenia, leucopenia and clinical jaundice. Main challenges and knowledge gaps to MiP control included diagnosis, relapsing malaria, mixed Plasmodium infection treatment, self-medication, low density infections and utility of artemisinin-based combination therapies. Conclusion All taken together, the findings could be immensely helpful to control MiP in malaria endemic areas.